Catalytic Liquid-phase Oxidation of Phenol under Mild Condition over Pt/CeO2–ZrO2–SnO2/SBA-16: Loading Optimization and Kinetic Analysis - Supandi, Abdul Rohman; Nunotani, Naoyoshi; Imanaka, Nobuhito (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Phenol removal through catalytic liquid-phase oxidation using oxygen gas is a green and efficient method. This study reports a systematic investigation of Pt catalysts supported on CeO2–ZrO2–SnO2 (CZSn)/SBA-16, focusing on the effect of SnO2 doping as well as CeO2–ZrO2–SnO2 and Pt loading as a comprehensive strategy to tune catalytic performance under mild conditions. This approach offers a more integrated optimization of catalyst structure and composition, leading to enhanced activity and new mechanistic insights into phenol removal over multicomponent oxide-supported Pt catalysts. XRD and H2-TPR analyses confirmed that 15 mol% Sn (CZSn0.15) provided optimal redox behavior, while higher Sn content led to phase separation. Catalytic tests at 80 °C and atmospheric pressure showed that Pt7CZSn0.1516SBA achieved the highest phenol removal (91%). Increasing CZSn loading up to 16 wt% improved activity, though further increase reduced surface area and performance. Meanwhile, Pt loading was optimal at 7 wt%. Kinetic analysis revealed the reaction followed pseudo-first-order kinetics with a rate constant of 0.39 h-1. The activation energy, derived from Arrhenius plots, was 57.7 kJ·mol-1. These findings demonstrate that optimized CZSn and Pt loadings significantly enhance phenol oxidation under mild conditions, offering a promising route for effective wastewater treatment.